2015
DOI: 10.1017/ice.2015.12
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Transmission Risk Through High-Level Disinfection of Transvaginal Ultrasound Transducer Handles

Abstract: Intracavity ultrasound transducer handles are not routinely immersed in liquid high-level disinfectants. We show that residual bacteria, including pathogens, persist on more than 80% of handles that are not disinfected, whereas use of an automated device reduces contamination to background levels. Clinical staff should consider the need for handle disinfection.Infect Control Hosp Epidemiol 2015;36(5): [581][582][583][584] Ultrasound transducers that contact broken skin or mucous membranes are considered semicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 8 publications
0
27
0
1
Order By: Relevance
“…Causative agents of urinary tract infections were also isolated from the handle including Staphylococcus haemolyticus, Staphylococcus saprophyticus and Enterococcus faecium. Handle contamination decreased to background levels after disinfection with an automated system designed for simultaneous disinfection of the probe handle and body 16 . Others have reported similar figures (83% when the handle is not disinfected) 11 .…”
Section: The Need For Infection Prevention and Controlmentioning
confidence: 80%
See 1 more Smart Citation
“…Causative agents of urinary tract infections were also isolated from the handle including Staphylococcus haemolyticus, Staphylococcus saprophyticus and Enterococcus faecium. Handle contamination decreased to background levels after disinfection with an automated system designed for simultaneous disinfection of the probe handle and body 16 . Others have reported similar figures (83% when the handle is not disinfected) 11 .…”
Section: The Need For Infection Prevention and Controlmentioning
confidence: 80%
“…Some probe manufacturers contraindicate immersion of probe handles in liquid disinfectant (since the handle is not fully sealed) while other manufacturers state that this is possible, but that the cable should not be immersed. This often results in confusion and immersion protocols exclusively for the probe body without consideration for handle disinfection 15 , 16 . A recent study reported 80.5% of vaginal ultrasound device handles were contaminated with clinically relevant bacteria following probe body immersion in glutaraldehyde per normal practice; S. aureus was isolated in 15.4% of these samples and one isolate was found to be methicillin‐resistant Staphylococcus aureus (MRSA).…”
Section: The Need For Infection Prevention and Controlmentioning
confidence: 99%
“…Therefore, official authorities in many countries are requesting a high-level disinfection for transvaginal probes [8], [9], [10]. Data are available that automated devices can reduce contamination of intracavity ultrasound probes to background levels [5]. One study showed that the automated device could reduce contamination with a success rate of 91.4% while a manual wipe method showed greater contamination (success rate of 78.8%) based on a study measuring bacterial contamination rates [12].…”
Section: Discussionmentioning
confidence: 99%
“…Among HPV certain high risk types like HVP16 and HPV18 are associated with cervical neoplasia. Several studies have shown intracavity ultrasound probes are contaminated with HPV following low level disinfection, and the virus can also be found throughout the gynaecological environment [2], [3], [4], [5], [6]. In a study with native HPV16 virions, it was shown that glutaral (GTA) and ortho -phthalaldehyde (OPA) were unable to inactivate the virus while hypochlorite and a peracetic acid (PAA)-silver based disinfectant were effective [7].…”
Section: Introductionmentioning
confidence: 99%
“…FA ZIT: Für die Desinfektion von starren Endosonografiesonden kommen unterschiedliche Verfahren zur Anwendung: Behandlung mit viruziden Wischtüchern [117,118], Wischtücher plus Schaumanwendung [105], Tauchdesinfektionsverfahren [117,119], ein vollautomatisches Desinfektionssystem mit Wasserstoffperoxid-Aerosol [107,109,120,121] oder Verfahren, bei denen eine UV-C-Bestrahlung eingesetzt wird [122,123]. Während bei der alleinigen Anwendung von Wischtüchern zwar die meisten Bakterien, aber nicht immer auch alle Viren und keine bakteriellen Sporen abgetötet werden, werden mit den anderen Verfahren alle Mikroorganismen, z. T. inkl.…”
Section: Infektionen Nach Endovaginaler Sonografieunclassified